Evaluating the ability of triaxial Schwarzschild modelling to estimate properties of galaxies from the Illustris simulation. Issue 4 (30th April 2019) - Jin, Yunpeng; Zhu, Ling; Long, R J; Mao, Shude; Xu, Dandan; Li, Hongyu; van de Ven, Glenn
Abstract: We evaluate the capabilities of Schwarzschild's orbit-superposition method by applying it to galaxies from the large-scale, high-resolution Illustris simulation. Nine early-type galaxies with a range of triaxiality are selected, and we create mock integral field unit data for five line-of-sight projections of each galaxy. Each of the 45 mock data sets is taken as an independent observed galaxy. Using van den Bosch's 2008 triaxial Schwarzschild implementation, we assess model estimates of various galaxy properties, covering mass profiles, intrinsic shapes, stellar orbit distributions, and velocity anisotropies. Total mass withinR_e is recovered well with average deviations within ±15 per cent. Stellar mass is underestimated by ∼24 per cent and dark matter overestimated by ∼38 per cent (assuming an NFW dark matter profile and allowing for degeneracy between stellar mass and dark matter mass). Using a gNFW profile, these values improve to ∼13 per cent for stellar mass and ∼18 per cent for dark matter. Axis ratio estimates show a moderate bias of Δ( b / a ) = 0.07 and Δ( c / a ) = 0.14 ( a ≥ b ≥ c ). Distributions of the orbit circularities λ z and λ x, representing rotation about the minor and major axes, are well reconstructed. Separating orbits into thermal categories, our models match the average fractions of these categories within 10 per cent. Velocity anisotropy is well estimated with values matching in the inner regions but becoming slightly radially biased in the outer regions. Overall, the galaxy property estimates we obtained using Schwarzschild modelling are not implausible and are representative of the simulated galaxies we modelled.